1993
DOI: 10.1139/v93-068
|View full text |Cite
|
Sign up to set email alerts
|

Aryl 1,5-dithia-2,4,6,8-tetrazocines. A synthetic, electrochemical, and structural investigation

Abstract: New preparative routes to the title compounds are reported in which the yields are substantially improved over previous methods. In one method, reaction of O2 with a mixture of XC6H,CN2S2+~1-and Ph,Sb leads to the products in 40-60% yield. In another, the reaction of the same salts with silylated amidines XC6H4C{NSiMe3}N(SiMe3)2 in a 1 : 1 mol ratio leads to the same compounds in 18-65% yield. The syntheses of 3,7-(XC6H,)2{CN2S2N,C), X = H, 4-CH,, 4-CH,O, 4 4 , 4-CF,, and 3-CF,, are reported. Mixed derivatives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 15 publications
4
33
0
Order By: Relevance
“…Clusters 2 provide well-resolved NMR spectra typical for diamagnetic species, i.e., without paramagnetic line broadening or unusual chemical shifts (5), whereas the parent dithiadiazole radicals 4 show broad featureless NMR spectra consistent with their paramagnetism. The 'H and I3c chemical shifts (Table 3) are within the range observed for a wide variety of aryl-C(NS-), compounds that we have previously studied (8). The samples of 4 were sealed under vacuum to prevent the facile reaction with oxygen (8a).…”
Section: Solution Studiesmentioning
confidence: 56%
“…Clusters 2 provide well-resolved NMR spectra typical for diamagnetic species, i.e., without paramagnetic line broadening or unusual chemical shifts (5), whereas the parent dithiadiazole radicals 4 show broad featureless NMR spectra consistent with their paramagnetism. The 'H and I3c chemical shifts (Table 3) are within the range observed for a wide variety of aryl-C(NS-), compounds that we have previously studied (8). The samples of 4 were sealed under vacuum to prevent the facile reaction with oxygen (8a).…”
Section: Solution Studiesmentioning
confidence: 56%
“…They recovered a mixture of symmetrically substituted products (14.5%) and unsymmetrically substituted products (3%) in a non-statistical ratio. Subsequent studies by Boeré et al (9) showed that unsymmetric dithiatetrazocines can be prepared by reaction of a dithiadiazolylium chloride salt with the silylated amidine in the minimum volume of refluxing MeCN. This scrambling reaction led to a statistical distribution of products (i.e., 50% unsymmetric product).…”
Section: Preparation and Crystal Growthmentioning
confidence: 99%
“…In our current studies, we utilized an alternative preparative route to DTTA rings, also developed by Boeré et al (9). The two dithiadiazolylium salts, [p-BrC 6 H 4 CNSSN]Cl and [p-O 2 NC 6 H 4 CNSSN]Cl, were prepared according to the literature method (17).…”
Section: Preparation and Crystal Growthmentioning
confidence: 99%
See 2 more Smart Citations